Development of IMA-3D Based E-Learning on Vocational Education in the 4D (Define-Design-Development, and Disseminate) Instructional Design Model - Mubarak, Ibnu; Danur Isnantyo, Fajar; Fawaid, Moh; Nurtanto, Muhammad; Suyitno, Suyitno; Asri , Sarwi; Supriyatna, Deddy (International Journal of Psychosocial Rehabilitation, 2020)
The ICT has become an important part of learning success in many countries. The addition of technology to learning online or mixed is more in demand by students in learning in vocational education. Previous researchers have developed the concept of interactive learning assisted by multimedia. However media research is limited in computer space and time of use. This study aims to develop interactive multimedia-AutoCAD 3D (IMA-3D) by measuring expert validation and user perception. The research method uses the 4D model approach (Define-Design-Development, and Disseminate). Expert validation consisted of media and language experts as well as material experts as considerations in the development in accordance with the context of vocational education media. As many as 34 respondents were involved in the use of IMA-3D with the characteristics of ± 18-20 years of age from various vocational schools with the organizers of the engineering curriculum. Data collection was carried out using a questionnaire with a measurement scale (RS. 1-5). Media and language validation results obtained an average of 79.20% (score. 99.00 from 125.00) in the agree category and validation of material experts obtained an average of 84.44% (score. 38.00 from 45.00) with a very agree category and both recommendations are valid. The user perception test results obtained an average of 72.16% (Score. 736 out of 1,020) with the category "Feasible or good". Interactive multimedia can increase new understanding and ease of learning, interests, talents, and motivation, learning more fun, and knowledge competency and practice are more directed at positive increases above 60%.